An olympiadic system of equations - Sušinskas, Jurgis; Mačys, Juozas Juvencijus (Lietuvos matematikos rinkinys, 2012)
Solution of an olympiadic system with three variables is considered. Solution of cubic equations is discussed. Some advices for young olympiadists are given.